UNDERSTANDING STUDENT EXPECTATION AND SATISFACTION TOWARS ONLINE LEARNING IN THE OPEN UNIVERSITY: A STUDY IN ARCHIPELAGIC AREA IN INDONESIA - Minrohayati, Minrohayati; Anfas, Anfas; Harsasi, Meirani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
The online tutorial is one of the learning methods used by students at the Open University (OP). One main obstacle in delivering online tutorial in OP is the accessibility of the internet, especially for the students living in archipelagic areas in Indonesia. This study aims to analyze the level of student satisfaction towards online tutorial activities at OP, especially for the Distance Learning Unit of OP Ternate that located in an archipelagic area with limited internet facilities. The population was the second-semester students come from various regions in Ternate. Research data were collected by distributing online questionnaires. The sample consisted of 24 respondents. Results showed that, in general, students were satisfied with online tutorial services. The level of student satisfaction towards internet access in the online tutorial was 96.04%, and for the aspect of presenting the learning materials, the satisfaction level was up to 100.77%. These findings indicated that student satisfaction exceeds their expectations. Furthermore, student satisfaction level towards the interaction aspect in the online tutorial was 89.92%. For the class assignment, the student satisfaction level was 97.05%. Keywords: access, assignment, learning material, online tutorial, student satisfaction